The effects of graded doses of heptachlor-A chlorinated hydrocarbon pesticide-on the reproductive performance of adult female (sprague dawley) rats. - Oduma, J.A. (University of Nairobi, 1998)
Heptachlor is a pesticide for foliar, soil and structural (buildings) applications. It is particularly effective against termites. However heptachlor and related chlorinated hydrocarbons pose a special problem because they are not easily biodegradable and therefore affect the ecology of the environment. In addition, being persistent and highly lipophilic, these compounds tend to accumulate in body fat of humans and animals that ingest contaminated food. In the developed countries, USA in particular, the use of heptachlor is now restricted to underground termite control and few other non-food related applications. However, the insecticide is still rampantly used in several developing countries against not only termites but also other pests like the cotton ball weevil and various ants that adversely decrease food and other agricultural production. Notably heptachlor has been reported to cause interstitial fibrosis of the kidney, atrophy of the testes, fibrosis of the heart and polyarteritis, while high accumulation in the ecosystem are through to be responsible for the thinning of eggshell and reproductive failure of certain species of birds. The effect of heptachlor on human reproductive health has not been adequately studied. Thus, apart from a few reports on its effect on litter size and mortality of neonates in laboratory rats and mice, there is little evidence of research undertaken to alucidate its effect on the mammalian reproductive system. This study was thus designed with the objective of investigating the effect of heptachlor on mammalian reproductive performance using the adult female laboratory rat as a model. To achieve this, adult (3-4 month old) normacyclic female Sprague Dawley rats were injected with com oil (controls) or with various doses of 5 mg, 20mg, 25mg, 30mg and 40mg/kg body weight heptachlor in corn oil (experimental) every 24 hrs for up to 18 days after which they were either mated or sacrificed. After the initial experiments, the higher dose treatments (25mg, 30mg and 40 mg/ kg bodyweight) were discontinued due to their lethal effect. For those that were mated, records were kept of their mating success (monitored by presence of sperms in vaginal smears), gestation length and litter size. Blood samples obtained from the sacrificed animals were assayed for progesterone, estradiol and some of the intermediate hormones namely pregnenolone, estrone, andostenedione 17a hdroxyprogesterone and dihydroepiandrosterone, by radioimmunoassay. Ovarian cells were isolated either from heptachlor treated rats or from untreated rats. These cells were incubated in minimum essential medium, MEM (Flow labs), either on their own, in the presence of gonadotrophins (LH and FSH), pregnenolone or androstenedione. Cells from untreated rats were incubated in MEM, either on their own or in the presence of heptachlor. A mixed population of ovarian cells or isolated follicular and luteal cells were used in these experiments. The incubation media were then analysed for the presence of the steroid hormones. Results showed that heptachlor significantly depressed (P<0.01) the body weights of the treated rats, in a dose dependent manner, when these were compared with the controls. There was a significant delay (P<0.001) in mating in treated rats compared to controls. In addition mean gestation length was elongated by between 3 to 10 days (P<0.05) and mean litter size decreased in treated rats (P<0.01) compared to controls. These effects were more pronounced at the higher heptachlor dose of 20mg/kg body weight compared to the lower dose (5mg/kg) and controls. Heptachlor significantly depressed plasma levels of progesterone and estradiol. The degree of depression and the level of significance depended on the dose and ranged from P<0.05 at the lower heptachlor dose to P<0.001 at the higher heptachlor dose. The same effect was seen in the levels of the intermediate hormones of progesterone and estradiol synthesis. In vitro production of the various hormones by ovarian cells from heptachlor-treated rats was lower than that of corn oil treated-controls, again the degree of suppression being dose dependent. This effect of heptachlor was demonstrated when the cells were incubated either in the presence or absence of gonadotrophins (LH and FSH) or in the presence or absence of substrate hormones (pregnenolone and androstenedione). Similar results were demonstrated in experiments where cells were taken from untreated rats and incubated with heptachlor. The effect of heptachlor on isolated follicular and luteal cells showed that heptachlor decreased hormone production by luteal cells more than follicular cells, the level of significance ranging from P<0.05 at the low heptachlor dose (0.06ng/well) to P<0.01 at the high heptachlor dose (0.6ng/well). It was concluded that heptachlor impacts negatively on several reproductive parameters, for example, mating success, litter size, body weights, cyclicity and hormonal levels in the female Sprague Dawley rat. The negative effects of heptachlor seen in in-vivo studies were corroborated by the results of in-vitro experiments indicating that heptachlor at sub-lethal doses could still act at the cellular level to cause physiological changes. The results show that the effects of heptachlor on the reproductive parameters measured in this study were dose dependent, with more adverse effects being achieved due to the higher levels of the pesticide being administered. The fact that the secretion of several steroid hormones were depressed suggest that heptachlor may be affecting some pathway intermediate/s or activity of one or more enzymes involved in steroid biosynthesis.